Preliminary study on the potential impact of probiotic combination therapy on Helicobacter pylori infection in children using 16S gene sequencing and untargeted metabolomics approach - Yan, Ya; Dong, Lingjun; Xu, Juan; Zhang, Zhijiao; Jia, Pengyan; Zhang, Jingmin; Chen, Weihong; Gao, Weiqi (Frontiers in Microbiology, 2024)
ObjectiveThe purpose of this study was to explore the potential mechanism of Helicobacter pylori (Hp) eradication by probiotic therapy through 16S rRNA gene sequencing technology and untargeted metabolomics.MethodsTwenty four Hp-infected children were recruited from the Shanxi Bethune Hospital, and 24 healthy children were recruited as a blank control group. Group A: fecal samples from 24 healthy children. Group B: fecal samples of 24 children with Hp infection. Group B1 (n = 15): fecal samples of group B treated with probiotic therapy for 2 weeks. Group B2 (n = 19): fecal samples of group B treated with probiotic therapy for 4 weeks. The above fecal samples were analyzed by 16S rRNA gene sequencing technology and untargeted metabolomics.ResultsThere was no significant difference in alpha diversity and beta diversity among the four groups, but many bacteria with statistical difference were found in each group at the bacterial genus level and phylum level. LEfSe results showed that in group B, Porphyromonadaceae, Shigella and other microorganisms related to intestinal microecological dysbiosis were enriched. And in group B2, abundant characteristic microorganisms were found, namely Bacillales and Prevotella. KEGG metabolic pathway enrichment analysis showed that groups B1 and B2 were involved in 10 metabolic pathways potentially related to probiotic treatment: purine metabolism, nitrogen metabolism, arginine biosynthesis, alanine, aspartic acid and glutamate metabolism, glyoxylic acid and dicarboxylic acid metabolism, unsaturated fatty acid biosynthesis, fatty acid extension, fatty acid degradation, pyrimidine metabolism, fatty acid biosynthesis.ConclusionProbiotic therapy can inhibit Hp to some extent and can relieve gastrointestinal symptoms, making it a preferred therapy for children with Hp infection and functional abdominal pain. Hp infection can reduce the diversity of intestinal microbes, resulting in the disturbance of intestinal microbiota and changes in the relative abundance of microbiota in children, while probiotic therapy can restore the diversity of intestinal microbes and intestinal microecological balance.